INCREASING STUDENT’S SPEAKING ABILITY THROUGH THINK PAIR SHARE - Ayu Jessica Frans; Jim R. Tuna; Nihta V. F. Liando (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research is to find out whethe the use of the Think Pair Share learning model could increase student’s speaking ability or not. This research was conducted at SMA Negeri 2 Tondano. This reaserch used quantitative research through pre-experimental dwsigh with one group pre-test and post-test. The subject of this research were all students of class XI IPS consisting of 18 students, who were taken based on considerations which were then included in the research class group. Research data were obtained from the ability of researcher to manage learning and students test results in this research is an oral test using speaking measurement which has 5 points of assessment. The results of this research shows that the mean score of pre-test is 2.11 and the mean score of post-test is 4.27. This means that the result of post-test is higher than the pre-test. It can be concluded that there is a positive significant in the use of Think Pair Share learning model in increasing student’s speaking ability at SMA Negeri 2 Tondano